Pemerolehan bahasa pada anak usia pascapubertas berkepribadian introvert di SMP-IT - Anita Angraini Lubis; Muttaqin Kholis Ali (JRTI (Jurnal Riset Tindakan Indonesia), 2021)
The title of this research is Language Acquisition in Postpubertal Age Children in Class IX. A SMP-IT Bunayya, Padangsidimpuan City. The purpose of the study is to obtain the results of the calculation of the Mean Length of Utterances (MLU) or the average length of utterances produced by postpubertal students with introverted personalities in writing. Explaining sentences produced by postpubertal students with introverted personalities in terms of simplicity and completeness of the basic sentences they have. Methods and Techniques used in this research: Listen (Sudaryanto 1993): SLC, SBLC, record, note, fishing, psychoneurolinguistic methods according to Nunan as well as formal and informal. The expected result of this research is that it can be used as a tool to find out how language is able to represent the personality possessed by humans. This research is also expected to be able to contribute to language teaching to postpubertal students with introverted personalities. It is hoped that this research will increase the insight of educators and the general public, especially about the language attitudes of post-pubertal students with introverted personalities and introverted groups in general.